Menata Ulang Layout Gudang Sparepart Menggunakan Metode Class Based Storage - Muhammad Rifqi Reza Fahlevi; Abi Hanif Dzulquarnain (Universitas Nusantara PGRI Kediri, 2025)
The ineffective warehouse layout at PT. XYZ causes a long picking process and operational inefficiency. This study uses a qualitative descriptive method. This study focuses on redesigning the layout of the spare parts warehouse using the Class-Based Storage (CBS) method to improve accessibility and minimize picking time. CBS groups items based on movement frequency, ensuring frequently accessed items are easily accessible. By analyzing existing challenges, including unorganized storage and unsystematic item placement, this study produces a new layout design. The results show a reduction in the total picking distance as well as increased efficiency in storing and identifying items, supporting smoother operational workflows and better resource management.